THU0121 Comparison of MTX Therapy with or without A Moderate Dose Glucocorticoid Bridging Scheme in Early Rheumatoid Arthritis Patients Lacking Classical Poor Prognostic Markers: Week 16 Results from the Randomized Multicenter Carera Trial. (10th June 2014) - De Cock, D.; Westhovens, R.; Corluy, L.; Joos, R.; Langenaken, C.; Taelman, V.; Raeman, F.; Ravelingien, I.; Vandevyvere, K.; Lenaerts, J.; Geens, E.; Geusens, P.; et al.
Abstract : Background: Whereas early intensive treatment to target is recommended in severe early Rheumatoid Arthritis (eRA), few data are available in patients presenting without bad prognostic markers. Objectives: To evaluate the efficacy and safety of methotrexate (MTX) monotherapy compared to MTX combined with a glucocorticoid (GC) bridging scheme during the first 16 weeks of treatment in "low risk" eRA patients. Methods: CareRA is a prospective two year investigator-initiated multicenter RCT rooted in daily practice. 400 eRA patients were stratified into a high or a low risk group. Low risk was defined as: - No erosions and ACPA and RF negative - Erosions, ACPA and RF negative and low disease activity (DAS28(CRP)≤3.2 - No erosions, ACPA and/or RF positive and low disease activity (DAS28(CRP) ≤3.2 Patients were randomized to 15 mg MTX, either with a bridging scheme of initially 30mg GCs tapered to 5 mg from week (W) 6 (Cobra Slim) or without GCs (MTX Tight Step Up (MTX-TSU)). Treatment modifications to target low disease activity were mandatory from W8 onwards. The primary outcome was remission (DAS28(CRP) <2.6) at W16 (ITT analysis). Secondary endpoints were good EULAR response, clinically meaningful HAQ response and HAQ=0. The Area Under the Curve (AUC) of DAS28(CRP) was calculated from baseline to W16. Adverse events (AEs) were registered. Results: We included 90 low risk patients: 24.4% were RF positive, 25.6% ACPA positive and 1.1% erosive, with a mean ± SD DAS28(CRP) of 4.53±1.62; 43 patients were randomized in the Cobra Slim and 47 in the MTX-TSU arm. At W16, 65.1% of the Cobra Slim and 46.8% of the MTX-TSU patients were in remission (p=0.081). A good EULAR response was achieved in 44.7% of MTX-TSU and 58.1% COBRA SLIM patients (p=0.202). A clinically meaningful HAQ response was reached in 53.2% of the MTX-TSU and 62.8% of the COBRA SLIM group (p=0.357). More patients had a HAQ=0 at W16 with the Cobra Slim (51.2%) compared to the MTX-TSU (23.4%) schedule (p=0.006). The mean± SD AUC of DAS28(CRP) was 11.18±4.25 and 13.84±4.58 for the Slim and MTX-TSU arm respectively (p=0.006). Treatment adjustments were performed in 27.9% of Slim and 40.4% of MTX-TSU patients (p=0.212). Until W16, therapy related AEs were reported in 39.5% of Slim and in 44.7% of MTX-TSU patients (p=0.622). Conclusions: Although the primary outcome, remission, was only numerically different after 16 weeks of treatment, cumulative disease activity over time and proportion with normalized HAQ were in favor of the Cobra Slim group, while related AEs didn't differ. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2144